Aerogel composite material capable of being repeatedly used and packaged under high-temperature condition and preparation method of aerogel composite material
By performing machine-adding, pre-sewing, pre-encapsulation and hole sealing treatment on the aerogel composite material, aerogel composite material with high density ceramic coating is solved, and the problem that aerogel composite material cannot maintain waterproof and oil-proof performance at high temperatures in the prior art is solved, and good heat insulation and waterproof performance in a high temperature environment of ≥650℃ is achieved, and the service life is significantly improved.
Patent Information
- Application Number
- CN202411832009.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing aerogel composite materials cannot maintain good waterproof and oil resistance at above 350°C, cannot be reused and are prone to powder and dust removal.
Aerogel composite material with a temperature resistance of more than 900°C is used to form an aerogel composite material with a high density ceramic coating through machine addition molding, pre-sewing, pre-encapsulation and hole sealing treatment. After heat treatment in a high temperature environment of ≥650℃, the material maintains good heat insulation and waterproofing and oil-proofing properties.
After multiple heat treatments of ≥650℃, the thermal insulation and waterproof and oil-proof properties of aerogel composites did not significantly attenuate, and their service life was significantly improved, and the problem of powder loss and dust removal was greatly reduced.
Smart Images

Figure CN119633702A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel heat-insulating composite materials, and in particular relates to an aerogel composite material that can be packaged and reused under high temperature conditions and a preparation method thereof. Background Art
[0002] Aerogel is a nanomaterial that is composed of nano-scale colloidal particles that aggregate to form a nanoporous network structure. It can be obtained through processes such as atmospheric drying, freeze drying or supercritical extraction. Its purpose is to evaporate the liquid in the wet gel and replace it with gas components, and maintain its three-dimensional porous nanomaterial in the gel state network. Aerogel materials have the characteristics of low density, large specific surface area, high porosity, and special thermal, optical, electrical and acoustic properties such as high temperature resistance, low thermal conductivity, low refractive index and low sound propagation speed. Aerogel is one of the lowest density solid materials in the world and can be used in aerospace, adsorbents, catalysts and life sciences.
[0003] In the field of thermal insulation, the main factors affecting the service life of aerogel thermal insulation materials are the following two points: 1. The mechanical properties and temperature resistance of aerogel itself are poor. After exceeding a certain threshold, the interface between aerogel and the reinforcing phase fails, causing the thermal insulation performance of the aerogel thermal insulation material to drop rapidly; 2. The hydrophobic properties of aerogel thermal insulation materials fail, causing the aerogel to absorb water molecules in the air, shortening the service life of aerogel thermal insulation materials.
[0004] Without considering external damage and overheating, the service life of aerogel is closely related to its hydrophobic properties. Aerogel insulation materials have a special three-dimensional network structure with a pore size smaller than air molecules, which can absorb water molecules in the air. There are a large number of hydrophilic groups such as hydroxyl groups on the surface of aerogel insulation materials, which easily adsorb water molecules in the air. When aerogel insulation materials absorb a large number of water molecules, it will cause changes in its internal structure, such as the collapse of the pore structure and a sharp increase in the thermal conductivity coefficient, which will greatly reduce the thermal insulation performance. In addition, the absorption of water molecules by aerogel insulation materials may also cause other problems, such as corrosion, changes in surface structure, etc., which further affect its thermal insulation performance and service life.
[0005] At present, in order to extend the storage period and service life of aerogel products, in the process of making aerogel composite materials, organic modifiers can be added to modify them to have good hydrophobic properties, such as hexamethyldisilazane. However, the temperature resistance of organic groups is usually below 350°C, and the hydrophobic property cannot be maintained below this temperature, which becomes the main factor hindering the repeated use of aerogels at high temperatures. At the same time, in applications in aerospace or new energy fields, there are usually some non-polar liquid substances (such as lubricating oils). Even if aerogel materials have good hydrophobicity, they will still absorb such non-polar liquid substances, resulting in a decrease in thermal insulation performance and cannot be reused for a long time.
[0006] In addition, inorganic (such as silica, alumina) aerogel materials are very brittle. Inorganic aerogel products will produce a lot of dust during storage, transportation, installation and use. The fallen silica and alumina particles will cause irreversible damage to instruments and equipment in normal use, affecting the test results of the instruments or the normal operation of the equipment. Environmental friendliness needs to be further improved.
[0007] At present, the aerogel composite materials prepared according to the preparation scheme disclosed in the art generally cannot maintain good waterproof and oil-proof properties at a temperature exceeding 350° C., can be reused, and reduce the phenomenon of powder and dust falling. Summary of the invention
[0008] In view of the problems in the prior art that aerogel composite materials cannot maintain good waterproof and oil-proof properties above 350°C, cannot be reused, and shed powder and dust, the present invention proposes a reusable packaged aerogel composite material under high temperature conditions and a preparation method thereof. The prepared aerogel composite material still maintains a good thermal insulation effect after heat treatment in a high temperature environment of ≥650°C, and has excellent waterproof and oil-proof properties. After multiple heat treatments at ≥650°C, its performance does not show obvious attenuation, which improves the service life of the aerogel composite material and greatly reduces the problem of powder and dust falling on the surface of the aerogel.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a reusable encapsulated aerogel composite material under high temperature conditions comprises the following steps:
[0011] S1, machining: machining the aerogel composite material to a set specification size;
[0012] The aerogel composite material is selected from composite materials with a temperature resistance of more than 900°C;
[0013] S2, pre-sewing: using the aerogel composite material after mechanical processing in S1 as the base material, selecting a lightweight heat-resistant fiber cloth to wrap it in shape, and selecting a thread of the same material for sewing to obtain an aerogel pre-sewn sample;
[0014] The light and heat-resistant fiber cloth has a surface density of ≥0.3g / cm 2 , selected from special fiber cloth, including but not limited to glass fiber cloth, quartz fiber cloth, alumina fiber cloth or zirconia fiber cloth;
[0015] S3, pre-packaging: using the aerogel pre-sewn sample obtained in S2 as a substrate, selecting a ceramic powder material that matches the thermal expansion coefficient of the lightweight heat-resistant fiber cloth, and evenly coating the ceramic coating on the surface of the aerogel pre-sewn sample by a thermal spraying process to obtain an aerogel pre-packaged sample;
[0016] The ceramic powder material is selected from one of silicon oxide, aluminum oxide, zirconium oxide, silicon nitride, glass-ceramics, silicon-boron-nitride oxide, and boron nitride;
[0017] The thickness of the ceramic coating is controlled to be 0.1 to 5 mm;
[0018] S4, sealing: the aerogel pre-packaged sample obtained in step S3 is coated with a sealing agent material on the pre-packaged sample through a coating process for sealing, and after curing, an aerogel composite material that can be reusable and packaged under high temperature conditions is obtained;
[0019] The sealing material is selected from a microcrystalline wax system sealing material, a silicone resin system sealing material, an aluminum-containing polymer sealing material or a phosphorus-containing polymer sealing material;
[0020] The obtained aerogel composite material which can be packaged and reused under high temperature conditions has a thermal conductivity growth rate of 10-20% at room temperature and a thermal conductivity growth rate of 15-30% at a high temperature of 300°C.
[0021] The composite material was heat treated in a muffle furnace at 650°C for 2 hours, and the treatment was repeated 10 times, with a mass loss rate of less than 2.1% and a mass moisture absorption rate of less than 1%.
[0022] It has excellent dielectric resistance, with thermal conductivity of 0.032W / (m·K)-0.043W / (m·K) at room temperature and 0.058W / (m·K)-0.089W / (m·K) at 300℃.
[0023] In the present invention:
[0024] The machining described in step S1 is to select aerogel composite materials as the substrate for mechanical processing. In order to ensure that the specifications and dimensions of the packaged aerogel composite materials products can meet the application requirements during the mechanical processing, the packaging material is no longer suitable for processing to avoid damage to the packaged sample structure. At the same time, it is necessary to chamfer the right-angle parts of the substrate to reduce the cracking of the coating caused by excessive stress and strain after the ceramic powder is sprayed on the right-angle parts of the sewn parts during the pre-packaging process and heated.
[0025] The composite material with a temperature resistance of more than 900° C. described in step S1 is selected from one of high-temperature resistant silica aerogel, alumina aerogel or alumina-silicon oxide aerogel composite materials, so as to avoid the temperature during the thermal spraying process causing the aerogel composite material structure to collapse and shrink.
[0026] The pre-sewing described in step S2, wherein the lightweight and heat-resistant fiber cloth used is mainly selected from special fiber cloth, including but not limited to glass fiber cloth, quartz fiber cloth, alumina fiber cloth and zirconium oxide fiber cloth, etc., whose main advantages are high temperature resistance, chemical corrosion resistance, and good insulation. The surface of the aerogel material is prone to powdering and falling off, and the ceramic coating is difficult to spray directly and well combined with the outer layer of the aerogel. It is easy to cause uneven force to cause the coating to crack and collapse. Choosing to sew a layer of fiber cloth outside the aerogel composite material can stabilize the shape of the aerogel product on the one hand, and on the other hand, the fiber cloth can be combined with the ceramic coating as a supporting structure to ensure that the composite material does not collapse, delaminate, crack, etc.
[0027] The surface density of the pre-sewn fiber cloth in step S2 should be ≥0.3g / cm 2 The fiber cloth with high surface density is denser and has better bonding effect with the sprayed ceramic material, which is beneficial to improve the density of the packaging layer. When the surface density of the fiber cloth is too small, the ceramic coating and the fiber cloth cannot be effectively combined into an integral structure, and are prone to cracking and collapse.
[0028] The pre-packaging described in step S3 adopts a ceramic coating material which is a ceramic powder material, mainly including one or more system materials such as silicon oxide, aluminum oxide, zirconium oxide, silicon nitride, microcrystalline glass, silicon boron nitride oxide, and boron nitride. Its main advantages are high temperature resistance, ablation resistance, and high density. The thermal expansion coefficient of the ceramic coating is well matched with the thermal expansion coefficient of aerogel materials such as silicon oxide and aluminum oxide and ceramic fiber cloth materials. It is not easy to crack and fall off due to the mismatch of expansion coefficient after heating. The performance of the ceramic powder material is better, and it is superior to a single powder material in terms of temperature resistance and density.
[0029] The pre-packaging described in step S3, wherein the thermal spraying process, the thickness of the thermally sprayed ceramic coating should be controlled at 0.1 to 5 mm, and further, 0.2 to 1 mm. The function of the ceramic coating is to form a dense insulating layer to ensure that water and other media in the environment do not enter the substrate. The dense ceramic coating has a high thermal conductivity. When the thickness of the ceramic coating is too high, the overall thermal conductivity of the composite thermal insulation material will increase, thereby affecting the thermal insulation performance of the material; and when the thickness of the ceramic coating reaches a certain value, the waterproof effect of the insulating layer is not significantly improved, and the excessive thickness of the ceramic coating also affects the overall density of the composite material. When the thickness of the ceramic coating is too thin, it is difficult to ensure the bonding effect between the ceramic coating and the fiber. On the other hand, when the thickness of the ceramic coating is too thin, the waterproof and oil-proof effect is reduced.
[0030] The sealing agent materials of step S4 mainly include microcrystalline wax system sealing materials, silicone resin system sealing materials, aluminum-containing polymer sealing materials, phosphorus-containing polymer sealing materials, etc. The main components of the composite material sealing agent include resin materials, glass fibers, curing agents and toughening agents, etc., and the main purpose is to improve the solid strength of the sealing agent, and the use temperature is also enhanced to a certain extent. However, since the main components still contain resin organic matter, the maximum use temperature is still difficult to reach above 350°C. Preferably, an inorganic composite material sealing agent with relatively good temperature resistance is preferably used, and its main components are inorganic salts, cement-based materials, diatomaceous earth and calcium sulfate, etc., so as to ensure that the aerogel composite material maintains good waterproof and oil-proof properties in an environment above 350°C.
[0031] The present invention also relates to an aerogel composite material that can be reusable and packaged under high temperature conditions, which is obtained by using the above-mentioned method for preparing an aerogel composite material that can be reusable and packaged under high temperature conditions. The obtained aerogel composite material that can be reusable and packaged under high temperature conditions has a thermal conductivity growth rate of 10-20% at room temperature and a thermal conductivity growth rate of 15-30% at a high temperature of 300°C.
[0032] The composite material was heat treated in a muffle furnace at 650°C for 2 hours, and the treatment was repeated 10 times, with a mass loss rate of less than 2.1% and a mass moisture absorption rate of less than 1%.
[0033] It has excellent dielectric resistance, with thermal conductivity of 0.032W / (m·K)-0.043W / (m·K) at room temperature and 0.058W / (m·K)-0.089W / (m·K) at 300℃.
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] 1. The method for preparing a reusable encapsulated aerogel composite material under high temperature conditions described in the present invention selects a ceramic powder material whose thermal expansion coefficient matches that of the fiber cloth for thermal spraying, firstly, the ceramic coating can be combined with the fiber cloth on the aerogel substrate to form a high-strength and high-density ceramic coating, and secondly, the coating is prevented from cracking and falling off due to the mismatch of expansion coefficients of the composite material of the ceramic coating and the aerogel sewn part after being heated.
[0036] 2. The method for preparing a reusable encapsulated aerogel composite material under high temperature conditions described in the present invention controls the thickness of the ceramic coating. The coating thickness affects the key performance indicators of the material such as thermal insulation and density. After pre-packaging, the surface of the material is a fiber ceramic composite coating with high strength, dense texture and close integration with the aerogel substrate. The beneficial effect is that it can effectively prevent the aerogel composite material from falling off. The ceramic coating is further densified by using a sealing material smaller than ceramic particles, and the sealing agent material is applied to the pre-packaged sample by brushing, spraying, dipping, etc., and the encapsulated aerogel composite product is obtained after curing.
[0037] 3. The aerogel composite material that can be reusably packaged under high temperature conditions described in the present invention has a dense ceramic coating after being treated with a ceramic coating and a sealing agent, which can effectively isolate water molecules in the air, so that the internal pore structure of the aerogel substrate will not collapse under high temperature conditions, thereby greatly improving the service life of the aerogel material. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a process flow chart of a method for preparing a reusable encapsulated aerogel composite material under high temperature conditions according to the present invention;
[0039] Figure 2 This is a graph showing the surface hydrophobic effect of an aerogel composite material that can be reusably packaged under high temperature conditions prepared in Example 5 of the present invention after being heat-treated 10 times in a muffle furnace at 650° C. for 2 hours;
[0040] Figure 3 This is a diagram of a medium resistance experimental test of a reusable encapsulated aerogel composite material prepared under high temperature conditions in Example 5 of the present invention (left: water; right: lubricating oil);
[0041] Figure 4 This is a diagram of dust adhesion test on the surface of an aerogel composite material that can be reusably packaged under high temperature conditions prepared in Example 5 of the present invention (left: substrate; right: aerogel composite material that can be reusably packaged under high temperature conditions);
[0042] Figure 5 This is a graph showing the surface hydrophobic effect of the sample prepared in Example 2 after 10 times of muffle furnace heat treatment at 650°C for 2h. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.
[0044] In the embodiments and comparative examples:
[0045] The mass moisture absorption data is measured in accordance with GB / T 5480-2008.
[0046] The room temperature thermal conductivity data is measured according to GB / T 10295-2008.
[0047] The high temperature thermal conductivity at 300°C is measured according to GB / T 10295-2008.
[0048] Embodiment 1:
[0049] A method for preparing a reusable encapsulated aerogel composite material under high temperature conditions comprises the following steps:
[0050] 1) Machining: machining a piece of silica aerogel thermal insulation composite material into an aerogel thermal insulation flat plate with a specification of 200×200×20 mm;
[0051] 2) Sewing: Use 0.1 mm thick quartz fiber cloth and quartz thread to sew the aerogel flat plate obtained in the above step, with a stitch distance of 20 mm, wrap the edges, and cut off the excess thread ends;
[0052] 3) Spraying: adopt a plasma spraying process, set the spraying power to 80kW, the spraying rate to 5kg / h, and the spraying angle to 60°, and evenly spray the silicon oxide powder material on the surface of the sewn sample in step 2), and control the thickness of the coating to be between 0.5mm. After cooling, grind the surface with sandpaper;
[0053] 4) Sealing: The aluminum-containing polymer sealing agent is evenly applied on the pre-packaged sample in step 3), and placed in a 100° C. oven for 2 hours for curing to obtain an aerogel composite material that can be reusable and packaged under high temperature conditions.
[0054] The obtained aerogel composite material for reusable packaging under high temperature conditions has the following properties:
[0055] The reusable packaged aerogel composite material is placed in a muffle furnace and heated and cooled as the furnace rises and falls, and heat treated at 650°C for 2 hours, which is repeated 10 times; the mass loss rate is 2.1%, the mass moisture absorption rate is 0.9%, and it has excellent medium resistance, the thermal conductivity at room temperature is 0.043W / (m·K), and the thermal conductivity at 300°C is 0.085W / (m·K).
[0056] Embodiment 2:
[0057] A method for preparing a reusable encapsulated aerogel composite material under high temperature conditions comprises the following steps:
[0058] 1) Machining: machining a piece of alumina aerogel thermal insulation composite material into an aerogel thermal insulation flat plate with a specification of 200×200×20 mm;
[0059] 2) Sewing: Use 0.1 mm thick quartz fiber cloth and quartz thread to sew the aerogel flat plate obtained in the above step, with a stitch distance of 20 mm, wrap the edges, and cut off the excess thread ends;
[0060] 3) Spraying: adopt a plasma spraying process, set the spraying power to 80kW, the spraying rate to 5kg / h, and the spraying angle to 60°, and evenly spray the silicon oxide powder material on the surface of the sewn sample in step 2), and control the thickness of the coating to be between 0.5mm. After cooling, grind the surface with sandpaper;
[0061] 4) Sealing: The aluminum-containing polymer sealing agent is evenly applied on the pre-packaged sample in step 3), and placed in a 100° C. oven for 2 hours for curing to obtain an aerogel composite material that can be reusable and packaged under high temperature conditions.
[0062] The obtained aerogel composite material for reusable packaging under high temperature conditions has the following properties:
[0063] The reusable packaged aerogel composite material was heat treated 10 times in a muffle furnace at 650°C for 2 hours; the mass loss rate was 1.9%, the mass moisture absorption rate was 0.8%, and it had excellent medium resistance, a thermal conductivity of 0.032 W / (m·K) at room temperature, and a thermal conductivity of 0.058 W / (m·K) at 300°C.
[0064] Embodiment 3:
[0065] A method for preparing a reusable encapsulated aerogel composite material under high temperature conditions comprises the following steps:
[0066] 1) Machining: machining a piece of silica aerogel thermal insulation composite material into an aerogel thermal insulation flat plate with a specification of 200×200×20 mm;
[0067] 2) Sewing: Use 0.1 mm thick quartz fiber cloth and quartz thread to sew the aerogel flat plate obtained in the above step, with a stitch distance of 20 mm, wrap the edges, and cut off the excess thread ends;
[0068] 3) Spraying: adopt a plasma spraying process, set the spraying power to 80kW, the spraying rate to 5kg / h, and the spraying angle to 60°, and evenly spray the silicon oxide / aluminum oxide mixed powder material on the surface of the sewn sample in step 2), and control the thickness of the coating to be between 0.5mm. After cooling, grind the surface with sandpaper;
[0069] 4) Sealing: The aluminum-containing polymer sealing agent is evenly applied on the pre-packaged sample in step 3), and placed in a 100° C. oven for 2 hours for curing to obtain an aerogel composite material that can be reusable and packaged under high temperature conditions.
[0070] The obtained aerogel composite material for reusable packaging under high temperature conditions has the following properties:
[0071] The reusable packaged aerogel composite material was heat treated 10 times in a muffle furnace at 650°C for 2 hours; the mass loss rate was 1.2%, the mass moisture absorption rate was 0.5%, and it had excellent medium resistance, a thermal conductivity of 0.041 W / (m·K) at room temperature, and a thermal conductivity of 0.087 W / (m·K) at 300°C.
[0072] Embodiment 4:
[0073] A method for preparing a reusable encapsulated aerogel composite material under high temperature conditions comprises the following steps:
[0074] 5) Machining: machining a piece of silica aerogel thermal insulation composite material into an aerogel thermal insulation flat plate with a specification of 200×200×20 mm;
[0075] 6) Sewing: Sewing the aerogel flat plate obtained in the above step with 0.1 mm thick alumina fiber cloth and alumina thread, with a stitch distance of 20 mm, edge treatment, and cutting off excess thread ends;
[0076] 7) Spraying: adopt a plasma spraying process, set the spraying power to 80kW, the spraying rate to 5kg / h, and the spraying angle to 60°, and evenly spray the silicon oxide powder material on the surface of the sewn sample in step 2), and control the thickness of the coating to be between 0.5mm. After cooling, grind the surface with sandpaper;
[0077] 8) Sealing: The aluminum-containing polymer sealing agent is evenly applied on the pre-packaged sample in step 3), and placed in a 100° C. oven for 2 hours for curing to obtain an aerogel composite material that can be reusable and packaged under high temperature conditions.
[0078] The obtained aerogel composite material for reusable packaging under high temperature conditions has the following properties:
[0079] The reusable packaged aerogel composite material was heat treated 10 times in a muffle furnace at 650°C for 2 hours; the mass loss rate was 1.7%, the mass moisture absorption rate was 0.8%, and it had excellent medium resistance, a thermal conductivity of 0.040 W / (m·K) at room temperature, and a thermal conductivity of 0.087 W / (m·K) at 300°C.
[0080] Embodiment 5:
[0081] A method for preparing a reusable encapsulated aerogel composite material under high temperature conditions comprises the following steps:
[0082] 9) Machining: machining a piece of silica aerogel thermal insulation composite material into an aerogel thermal insulation flat plate with a specification of 200×200×20 mm;
[0083] 10) Sewing: Sewing the aerogel flat plate obtained in the above step with 0.1 mm thick quartz fiber cloth and quartz thread, with a stitch distance of 20 mm, edge treatment, and cutting off excess thread ends;
[0084] 11) Spraying: adopt a plasma spraying process, set the spraying power to 80kW, the spraying rate to 5kg / h, and the spraying angle to 60°, and evenly spray the silicon oxide powder material on the surface of the sewn sample in step 2), and control the thickness of the coating to be between 1mm. After cooling, grind the surface with sandpaper;
[0085] 12) Sealing: The aluminum-containing polymer sealing agent is evenly applied on the pre-packaged sample in step 3), and placed in a 100° C. oven for 2 hours for curing to obtain an aerogel composite material that can be reusable and packaged under high temperature conditions.
[0086] The obtained aerogel composite material for reusable packaging under high temperature conditions has the following properties:
[0087] The reusable packaged aerogel composite material was heat treated 10 times in a muffle furnace at 650°C for 2 hours; the mass loss rate was 0.5%, the mass moisture absorption rate was 0.7%, and it had excellent medium resistance, a thermal conductivity of 0.043 W / (m·K) at room temperature, and a thermal conductivity of 0.089 W / (m·K) at 300°C.
[0088] like Figure 2 As shown in FIG. 5 , a reusable encapsulated aerogel composite material prepared in Example 5 under high temperature conditions was subjected to a muffle furnace heat treatment at 650° C. for 2 h for 10 times to show the surface hydrophobic effect; Figure 2 As shown, a hydrophobic experiment was carried out on an aerogel composite material that can be reusably packaged under high temperature conditions obtained in Example 5. After multiple heat treatments at 650°C, its hydrophobic performance did not significantly decay, thereby improving the service life of the aerogel composite material.
[0089] like Figure 3 As shown, a reusable encapsulated aerogel composite material obtained in Example 5 under high temperature conditions was subjected to a medium resistance test. After being immersed in water and lubricating oil for 72 hours, the mass increase rate was ≤3%, and the mass moisture absorption rate was ≤3%; after multiple heat treatments at 650°C, its performance did not significantly decay, which improved the service life of the aerogel composite material and greatly reduced the problem of powder and dust falling on the surface of the aerogel;
[0090] like Figure 4 As shown, the surface of the reusable packaged aerogel composite material obtained in Example 5 under high temperature conditions was subjected to an adhesion test, and the ash on the surface of the reusable packaged aerogel composite material was significantly reduced.
[0091] Comparative Example 1:
[0092] The difference between Comparative Example 1 and Example 1 is that an organic silicone resin sealing agent is used instead of an aluminum-containing polymer sealing agent for sealing treatment, and the rest is the same as Example 1, including the following steps:
[0093] 1) Machining: machining a piece of silica aerogel thermal insulation composite material into an aerogel thermal insulation flat plate with a specification of 200×200×20 mm;
[0094] 2) Sewing: Use 0.1 mm thick quartz fiber cloth and quartz thread to sew the aerogel flat plate obtained in the above step, with a stitch distance of 20 mm, wrap the edges, and cut off the excess thread ends;
[0095] 3) Spraying: adopt a plasma spraying process, set the spraying power to 80kW, the spraying rate to 5kg / h, and the spraying angle to 60°, and evenly spray the silicon oxide powder material on the surface of the sewn sample in step 2), and control the thickness of the coating to be between 0.5mm and 1mm. After cooling, polish the surface with sandpaper;
[0096] 4) Sealing: The silicone resin sealing agent is evenly applied on the pre-packaged sample in step 3), and placed in a 100° C. oven for 2 hours for curing to obtain an aerogel composite material that can be reusable and packaged under high temperature conditions.
[0097] The obtained aerogel composite material for reusable packaging under high temperature conditions has the following properties:
[0098] The reusable packaged aerogel composite material was heat treated 10 times in a muffle furnace at 650°C for 2 hours; the mass loss rate was 2.0%, the mass moisture absorption rate was 13.7%, and it had excellent medium resistance, a thermal conductivity of 0.042 W / (m·K) at room temperature, and a thermal conductivity of 0.086 W / (m·K) at 300°C.
[0099] The results show that:
[0100] The silicone resin sealant used in Comparative Example 1 has relatively poor temperature resistance. After ten heat treatments in a muffle furnace at 650°C for 2h, the sealant coating was destroyed by the high temperature, resulting in a higher mass moisture absorption rate, indicating that the surface waterproofing effect has failed.
[0101] Comparative Example 2:
[0102] The difference between Comparative Example 2 and Example 1 is that quartz fiber cloth is not used for the overlocking treatment. The other steps are the same as Example 1, including the following steps:
[0103] 1) Machining: machining a piece of silica aerogel thermal insulation composite material into an aerogel thermal insulation flat plate with a specification of 200×200×20 mm;
[0104] 2) Spraying: adopt a plasma spraying process, set the spraying power to 80kW, the spraying rate to 5kg / h, and the spraying angle to 60°, and evenly spray the silicon oxide powder material on the surface of the aerogel insulation plate in step 1, and control the thickness of the coating to be between 0.5mm. After cooling, polish the surface with sandpaper;
[0105] 3) Sealing: The aluminum-containing polymer sealing agent is evenly applied on the pre-packaged sample in step 3), and placed in a 100° C. oven for 2 hours for curing to obtain an aerogel composite material that can be reusable and packaged under high temperature conditions.
[0106] The obtained aerogel composite material for reusable packaging under high temperature conditions has the following properties:
[0107] The reusable packaged aerogel composite material was placed in a muffle furnace for heat treatment at 650°C for 2h for 10 times; the mass loss rate was 24.2%, the mass moisture absorption rate was 32.3%, the thermal conductivity at room temperature was 0.041W / (m·K), and the thermal conductivity at 300°C was 0.082W / (m·K).
[0108] Figure 5 This is a picture of the surface of the reusable packaged aerogel composite material of Comparative Example 2 after heat treatment 10 times in a muffle furnace at 650°C for 2h.
[0109] The results show that:
[0110] For the sample in Comparative Example 2 that was not treated with fiber cloth wrapping, after 10 times of heat treatment in a muffle furnace at 650°C for 2h, the mass moisture absorption rate increased significantly. Combined with the pictures, the ceramic coating of the sample in Comparative Example 2 fell off.
[0111] Table 1: Comparison of properties of reusable encapsulated aerogel composites prepared by different processes after heat treatment in a muffle furnace at 650℃ for 2h for ten times:
[0112]
[0113] The results show that:
[0114] 1. After heat treatment at 650°C, the aerogel composite material prepared by the present invention can still maintain good thermal insulation effect. Taking the silica aerogel composite material obtained in Example 1 as an example, the thermal conductivity of the aerogel thermal insulation composite material product at room temperature is ≤0.037W / (m·K), and the thermal conductivity at 300°C is ≤0.071W / (m·K). Using this as a substrate, a reusable encapsulated aerogel composite material with a specification of 200×200×20mm is prepared. The thermal conductivity at room temperature is ≤0.043W / (m·K), and the thermal conductivity at 300°C is ≤0.087W / (m·K). The thermal conductivity at room temperature is increased by 16.21%, and the thermal conductivity at 300°C is increased by 19.72%, but it can still maintain good thermal insulation effect and has excellent waterproof and oil-proof properties. Figure 3 As shown in the figure, the inventors conducted a medium resistance experiment. After immersing in water and lubricating oil for 72 hours, the mass increase rate was ≤3%, and the mass moisture absorption rate was ≤3%. After multiple heat treatments at 650°C, there was no obvious attenuation of its performance, which improved the service life of the aerogel composite material and greatly reduced the problem of powder and dust falling on the surface of the aerogel. Figure 4 As shown, the inventors conducted an adhesion test on the aerogel surface, and the ash on the surface of the reusable packaged aerogel composite material was significantly reduced.
[0115] 2. By comparing Example 1 with Comparative Example 1, the silicone resin sealant is an organic sealant with relatively poor temperature resistance. After heat treatment in a muffle furnace at 650°C for 2h for ten times, the sealant coating is destroyed by high temperature, resulting in a higher mass moisture absorption rate, indicating that the surface waterproofing effect has failed. The aluminum-containing polymer sealant is an inorganic sealant. After heat treatment in a muffle furnace at 650°C for 2h for ten times, the mass moisture absorption rate is still maintained at ≤3%, indicating that the inorganic sealant has better temperature resistance.
[0116] 3. By comparing Example 1 with Comparative Example 2, the sample that has not been treated with fiber cloth wrapping has a significantly increased mass moisture absorption rate after 10 times of muffle furnace heat treatment at 650°C for 2h. At the same time, combined with the pictures, the ceramic coating of the sample in Comparative Example 2 has fallen off, indicating that the quartz fiber cloth can enhance the strength of the ceramic coating and will not cause the coating to fall off due to high temperature.
[0117] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing a reusable encapsulated aerogel composite material under high temperature conditions, characterized in that: The following steps are involved: S1, machining: machining the aerogel composite material to a set specification size; The aerogel composite material is selected from composite materials with a temperature resistance of more than 900°C; S2, pre-sewing: using the aerogel composite material after mechanical processing in S1 as the base material, selecting a lightweight heat-resistant fiber cloth to wrap it in shape, and selecting a thread of the same material for sewing to obtain an aerogel pre-sewn sample; The light and heat-resistant fiber cloth has a surface density of ≥0.3g / cm 2 , selected from special fiber cloth, including but not limited to glass fiber cloth, quartz fiber cloth, alumina fiber cloth or zirconia fiber cloth; S3, pre-packaging: using the aerogel pre-sewn sample obtained in S2 as a substrate, selecting a ceramic powder material that matches the thermal expansion coefficient of the lightweight heat-resistant fiber cloth, and evenly coating the ceramic coating on the surface of the aerogel pre-sewn sample by a thermal spraying process to obtain an aerogel pre-packaged sample; The ceramic powder material is selected from one of silicon oxide, aluminum oxide, zirconium oxide, silicon nitride, glass-ceramics, silicon-boron-nitride oxide, and boron nitride; The thickness of the ceramic coating is controlled to be 0.1 to 5 mm; S4, sealing: the aerogel pre-packaged sample obtained in step S3 is coated with a sealing agent material on the pre-packaged sample through a coating process for sealing, and after curing, an aerogel composite material that can be reusable and packaged under high temperature conditions is obtained; The sealing material is selected from a microcrystalline wax system sealing material, a silicone resin system sealing material, an aluminum-containing polymer sealing material or a phosphorus-containing polymer sealing material; The obtained aerogel composite material which can be packaged and reused under high temperature conditions has a thermal conductivity growth rate of 10-20% at room temperature and a thermal conductivity growth rate of 15-30% at a high temperature of 300°C. The composite material was heat treated in a muffle furnace at 650°C for 2 hours, and the treatment was repeated 10 times, with a mass loss rate of less than 2.1% and a mass moisture absorption rate of less than 1%. It has excellent dielectric resistance, with thermal conductivity of 0.032-0.043W / (m·K) at room temperature and 0.058-0.087W / (m·K) at 300℃.
2. The method for preparing a reusable encapsulated aerogel composite material under high temperature conditions according to claim 1, characterized in that: In the pre-packaging described in step S3, the thermal spraying process is performed, and the thickness of the thermally sprayed ceramic coating is controlled to be 0.2 to 1 mm.
3. An aerogel composite material that can be reusable and packaged under high temperature conditions, characterized in that: The composite material is obtained by the method for preparing a reusable encapsulated aerogel composite material under high temperature conditions as claimed in claim 1 or 2, wherein the growth rate of the thermal conductivity of the composite material at room temperature is 10-20%, and the growth rate of the thermal conductivity at 300°C is 15-30%; The composite material was heat treated in a muffle furnace at 650°C for 2 hours, and the treatment was repeated 10 times, with a mass loss rate of less than 2.1% and a mass moisture absorption rate of less than 1%. It has excellent dielectric resistance, with thermal conductivity of 0.032-0.043W / (m·K) at room temperature and 0.058-0.087W / (m·K) at 300℃.
Citation Information
Patent Citations
Novel high temperature resistant heat insulation material and preparation thereof
CN101469803A
Silicon dioxide aerogel composite material and preparation method and application thereof
CN109336545A
Multilayer aerogel composite material
CN114559711A
Reusable wave-transparent heat-insulating aerogel material and preparation method thereof
CN118754597A
High temperature, hydrophobic, flexible aerogel composite and method of making same
US10633256B1